Estimating sea bottom shapes for grounding damage calculations. (January 2016) - Sormunen, Otto-Ville Edvard; Castrén, Antti; Romanoff, Jani; Kujala, Pentti
Abstract: Groundings are among the most common and serious maritime accidents. The shape of the sea bottom is one of the important factors that determine the extent of grounding damage on ships, including loss of watertightness. This paper presents a four-step methodology for mathematically analyzing sea bottom shapes, where individual peaks are identified and isolated from larger datasets. To these individual peaks mathematical models are fitted and the goodness of the fit is evaluated. The aim is to develop mathematical rock models that can be used in grounding damage analysis. The method is applied to bottom topography data from the two busiest tanker harbors in Finland. As potential mathematical rock models common assumptions found in literature as well as new suggestions are used. It was observed that rocks vary in shape and size locally as well as between different geographical areas. This highlights the need to have rock models that are flexible enough to model a wide range of sizes and shapes so that the local conditions can be taken into account. This includes modeling asymmetrical shapes, which is not taken into account in the current models. The analysis results suggest using a binormal function to describe the bottom shape: This model gives overall better goodness-of-fit test results than the cone and polynomial models. In the data the binormal model can model well the also the bottom shapes where the polynomial and conical models had a good fit in statistical terms. Although the paper discusses data from the Gulf of Finland, the framework for analyzing bottom shapes is expected to be applicable to other sea areas as well. Highlights: Bottom hydrographical data from busiest Finnish tanker channels was analyzed. Rock shapes show large scatter in terms of radius and depth change. Exact shape and size of rock important for grounding damage analysis. A systematic approach for isolating, classifying and mathematically modeling individual rocks from datasets was developed. Binormal function proposed to describe bottom shape instead of current conical or polynomial assumptions.